Exploring the Dynamics of Technological Innovations in Human Resource Development and Its Economic Implications - Muhlis; Syamsu Rijal (International journal of technology and education research, 2026)
Indonesia has been at a really important turning point over the past ten years: the very precise, effective world of technology is colliding with what people are capable of. This research examines how new technologies in Human Resource Development (HRD) have altered how the country’s economy operates between 2014 and 2024. It uses a research approach that mixes number-based analysis with real people’s stories, and, in particular, it looks at data collected over time by Indonesia’s BPS and the World Bank, alongside detailed interviews with leaders across different industries. What’s been discovered is that the use of HR tech increased by 126.2%, and, with that, it didn't simply make workers 4.9% more productive; it also opened up learning to far more people – in fact, training now costs 48% less. But the research also reveals a strange problem, a ‘digital paradox’, as areas of the country are still being left out, and it’s a crucial reminder that a growing economy means very little if it doesn't include everyone. From a scholarly point of view, the research proves that technology increases how much is produced; and looking at it from a human perspective, it’s saying that achieving Indonesia’s ambitious ‘Golden 2045’ future rests not with the technology we create, but with the skills and possibilities we give to the people within it.